Characterization of the neutron flux on the surface of a liquid water target intended for 18F production. (July 2021) - Košťál, Michal; Schulc, Martin; Losa, Evžen; Matěj, Zdeněk; Cvachovec, František; Mravec, Filip; Brijar, Filip; Czakoj, Tomáš; Šimon, Jan; Vadják, Šimon; Antoš, Michal; Přenosil, Václav; et al.
Abstract: 18 F is an important radioisotope used in nuclear medicine for diagnostic purposes. It is produced most often via 18 O (p, n) 18 F reaction. During its production, the oxygen contained in the H2 18 O molecules placed in the cooled target is irradiated by accelerated protons. The production of each 18 F atom is accompanied by anisotropic high-energy neutron emission, which is a problem for ensuring radiation safety. These neutrons are responsible for the high radiation dose in a cyclotron pit during 18 F production as well as for activation of cyclotron components or might be responsible even for target material changes due to their high penetration properties. A precise characterization of a neutron field on the surface of the liquid water target, used for 18 F production, is presented. The neutron flux characterization is performed both by using large-area activation detectors and stilbene detectors at 1 m from the target in a forward direction. The experiments show significant discrepancies between calculated and measured reaction rates in higher threshold reactions 58 Ni(n, x) 57 Co and 51 V (n, α) 48 Sc, confirming that the current neutron production reaction models are not suitable for the characterization of the secondary neutrons leaking from the target. Highlights: Measurement of neutron leakage spectra in forward direction. Measurement of reaction rates in various positions on IBA target. Calculation of neutron field in all measured positions. Discrepancies between calculation and experiment.